Degree of embedding knowledge economy skills in the social studies courses for the primary stage in The Kingdom of Saudi Arabia - Al-Nefaie, Mashael Saleh; Najmuldeen, Hanan AbdelJalil (Journal of Curriculum and Teaching Methodology, 2023)
The research aims to determine was to determine how much knowledge economy skills were covered in the main social studies curriculum in the Kingdom of Saudi Arabia. The two scholars created a list of knowledge economy skills that should be included in social studies courses for the elementary level, at the rate of three books taught in the first, second, and third semesters of the academic year (1444). The cognitive, economic, and technical domains make up the final form of it, which comprises of five key fields. The social domain, the national domain, under which ten sub-skills and (48) indicators are included, and in light of which a content analysis tool was prepared, and the results showed a discrepancy in the inclusion of knowledge and economic skills in the Content of social studies courses for the primary stage, as the knowledge domain came in first place with (46.23%), followed by the national field by (32.73%), the economic field by (12.42%), the social field by (11.96%), followed by the technological field by (2.83%). The two researchers made a number of recommendations. There is a growth in interest in the technological, social, and economic domains of economic knowledge and skills. To incorporate skills that are not included in the content or have a low degree of inclusion; to draw on the knowledge economy skills list; and to take use of the present research’s findings. Moreover, activities that promote subject themes and aid in the development of knowledge economy skills are included.